Managing engineering and technology an introduction to management for engineers - Morse, Lucy C. (Prentice-Hall international series in industrial and systems engineering, 2007)
Tailored to the needs of the technical professional, this handbook is designed to teach engineers, scientists and other technologists the basic management skills they will need to be effective throughout their careers. Traces the historical development and describe the functions of management, fromplanning, and decision making to organizing, staffing, leading, motivating, and controlling. Includes an expanded discussion of engineering ethics. Describes the nature and application of management principles throughout the technology product/project life cycles. Discusses the transition from technical performer to technical management; the position of women and minorities in engineering management; effective time management, and the importance of professional ethics and conduct. For engineers, scientists and other technical professionals who need to enhance their management skills.